Diaphragmatic pacemaker-induced ventricular tachycardia leading to cardiac arrest: a case report. Issue 9 (7th September 2021) - Dong, Tony; Chami, Tarek; Janus, Scott; Hajjari, Jamal; Fernandez, Antonio Sotolongo; Josephson, Richard
Abstract: Background: Diaphragmatic pacemakers are used to assist respiration in ventilator-dependent patients. Electromagnetic interference with intrinsic cardiac electrical activity is a theoretical risk but has never been reported in the literature. This case highlights a serious complication of cardiac arrest as a result of diaphragmatic pacing. Case summary: We report a quadriplegic patient with recent diaphragmatic pacemaker implantation who presented with ventricular tachycardia leading to cardiac arrest. Extensive workup was negative for other aetiologies for ventricular arrhythmias. Reduction of the left-sided diaphragmatic pacemaker voltage resulted in cessation of ventricular ectopy. Discussion: Diaphragmatic pacing at high voltages can cause unwanted transmission of impulses to the cardiac myocytes as a rare complication. This should be noted as a possible complication of intramuscular diaphragmatic pacing, and efforts should be taken to circumvent this risk in the future.